2000
DOI: 10.1085/jgp.116.5.637
|View full text |Cite
|
Sign up to set email alerts
|

A Hot Spot for the Interaction of Gating Modifier Toxins with Voltage-Dependent Ion Channels

Abstract: The gating modifier toxins are a large family of protein toxins that modify either activation or inactivation of voltage-gated ion channels. ω-Aga-IVA is a gating modifier toxin from spider venom that inhibits voltage-gated Ca2+ channels by shifting activation to more depolarized voltages. We identified two Glu residues near the COOH-terminal edge of S3 in the α1A Ca2+ channel (one in repeat I and the other in repeat IV) that align with Glu residues previously implicated in forming the binding sites for gating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 46 publications
3
83
0
Order By: Relevance
“…It is likely that these three amino acid residues form the primary component of the receptor site for α-scorpion toxins. Amino acid residues aligned with Phe1610 and Glu1613 contribute to the ω-agatoxin receptor site in Ca V 2.1 channels (19,20) and the hanatoxin and grammotoxin receptor sites in K V channels (21,22). Thus, these studies reveal a common five-residue motif of two hydrophobic residues in positions 1 and 2 followed by Glu in position 5 (ΦΦXXE) that may contribute to the actions of all of these gating modifier toxins (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that these three amino acid residues form the primary component of the receptor site for α-scorpion toxins. Amino acid residues aligned with Phe1610 and Glu1613 contribute to the ω-agatoxin receptor site in Ca V 2.1 channels (19,20) and the hanatoxin and grammotoxin receptor sites in K V channels (21,22). Thus, these studies reveal a common five-residue motif of two hydrophobic residues in positions 1 and 2 followed by Glu in position 5 (ΦΦXXE) that may contribute to the actions of all of these gating modifier toxins (4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that the conserved acidic amino acid residue E1613 in IVS3-S4 is involved in binding of α-scorpion toxins (14), and subsequent studies showed that analogous amino acid residues are important for binding of other toxins to voltage-gated K + and Ca 2+ channels (19)(20)(21)(22). In this study, we identified amino acid residues in the ISS2-S6 loop, IVS1-S2 loop, and IVS3 segment as components of neurotoxin receptor site 3, and this information was used to generate a molecular model of the toxin-receptor complex in the resting state using the Rosetta Membrane program.…”
mentioning
confidence: 99%
“…Interestingly HWTX-I also seems to inhibit N-type calcium channels (36), although the molecular determinants of this interaction are not known, and it is not clear whether this calcium channel inhibition might involve S4 segment trapping. Acidic residues in S3-S4 linkers are important determinants of -agatoxin-IVA binding to P-type calcium channels (34) and hanatoxin binding to Kv1.2 potassium channels (54). Our data support the proposal that there is a conserved binding mechanism for gating modifier toxins that inhibit the activation of voltage-gated ion channels (34).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the toxins that modify activation or inactivation of voltage-gated ion channels bind to the S3-S4 region(s) of the channels (10,34) that are probably the most external parts of the voltage sensors on voltage-gated ion channels. Although several tarantula toxins that inhibit activation of potassium channels interact with the S3-S4 region, it is not known whether tarantula toxins that inhibit sodium channel activity interact with S3-S4 regions.…”
Section: Effects Of Subsaturating Concentrations Of Hwtx-iv On Activamentioning
confidence: 99%
“…Swartz, 2000Swartz, 2000 illustrates the alignment of the S3 S4 loops in domain IV of Na 1.2 channels containing the -scorpion toxin and sea Scheme 1 conservative amino acid substitutions in order to retain protein expression and function, it is likely that the substituted amino acid residues at these critical positions retain a substantial contribution to the residual low-affinity binding of CssIV and therefore that this is a lower limit of their contribution to high affinity binding. The three amino acid residues involved in the formation of the -scorpion toxin receptor β site on IIS3 S4 linker of Na 1.2 channels are quite different in sequence context from those forming the interaction site for -scorpion …”
Section: Interaction Sites For Voltage-sensor Trappingmentioning
confidence: 99%